Improving university mental health - Morris, Jane 1951- (Cambridge University Press, 2024)
In the aftermath of the COVID-19 pandemic, and in the midst of global economic turmoil, university students and staff face unprecedented challenges to their mental-wellbeing. With a focus on the UK experience, this book presents a thorough examination of the mental health challenges faced in university communities. Key topics covered include the role of alcohol, social media, and financial pressures, as well as specific challenges presented by ethnicity and gender. The book draws on case studies and media extracts to demonstrate the reality of mental health within universities in the current climate, and includes practice points and suggestions for action to improve policy going forward. This is a much-needed handbook for mental health professionals, including psychiatrists, clinical psychologists and GPs, social support workers and counsellors, as well as teaching staff, students and parents.